Utilization of fermented and enzymatically hydrolyzed soy press cake as ingredient for meat analogues. (1st August 2022) - Razavizadeh, Seyedmahmood; Alencikiene, Gitana; Vaiciulyte-Funk, Lina; Ertbjerg, Per; Salaseviciene, Alvija
Abstract: The aim of the present study was to improve the properties of soy press cake to be utilized as an ingredient of meat analogues. Soy press cakes were fermented with lactobacillus strains, and separately hydrolyzed by cellulase/xylanase mixture and α-amylase. Meat analogues were produced with 10% fermented or hydrolyzed soy press cakes. The effect of applied processes on protein oxidation, physical and functional properties of soy press cakes were analyzed, as well as sensory and textural properties of meat analogues. The results indicated that soy press cake was a suitable source of fibre and energy with low content of saturated fatty acids, and provided plant-based proteins and essential amino acids. The study demonstrated the potential of lactic acid fermentation, and enzymatic hydrolysis to improve water- and oil-holding capacity and reduce protein oxidation in soy press cakes. L. acidophilus 336 and cellulase/xylanase mixture were recommended for fermentation and hydrolysis of soy press cakes, respectively, regarding reduction of protein oxidation. Fermentation of soy press cakes with L. plantarum P1 improved the texture of meat analogues. Press cakes fermentation reduced bitterness, increased juiciness, and balanced the taste of meat analogues. Fermented soy press cake was recommended for the production of meat analogues. Highlights: This research was the 1st application of fermented soy press cake in meat analogue. Fermentation and hydrolysis improved the functional properties of soy press cakes. Protein oxidation in soy press cakes was reduced after fermentation and hydrolysis. Fermented soy press cakes improved sensory quality of the meat analogues. L. plantarum P1 is recommended for the fermentation of soy press cakes.